Power to the people—And then? A multilevel leadership perspective on organizational decentralization - Hendrik Huettermann; Stefan Berger; Max Reinwald; Heike Bruch (Human Resource Management, 2024)
As organizations strive for more flexibility, decentralized decision-making has been at the core of many modern HR approaches. Yet, on a company-wide scale, it remains unclear whether decentralized decision-making structures improve organizational performance. Our study aims to illuminate prior ambiguous evidence by examining an employee-level mechanism underlying the organizational-level relationship between decentralization and performance, and scrutinizing the critical role of formal leaders for empowering employees in decentralized structures. Integrating the perspective of organizational structure as opportunities and constraints with social information processing theory, we argue that transferring decision-making authority to lower organizational levels positively affects employees' emergent leadership, but only to the extent that direct supervisors engage in empowering leadership and guide employees' behaviors in decentralized structures. Our predictions are supported by a multilevel, multisource field study of 5807 individuals across 144 companies. We further find that emergent leadership yields a positive effect on organizational performance. By developing a multilevel model that explicates both an employee-level mechanism and a contingency of the decentralization–organizational performance link, our study enriches understanding of the key role that formal leaders play for achieving the strategic goals of decentralized decision-making in organizations.
Keywords: 650; decentralized decision-making; emergent leadership; empowering leadership; organizational performance; organizational structure